The Core Roles of Transparency and Accountability in the Governance of Global Health Public–Private Partnerships. Issue 3 (3rd July 2018) - Reich, Michael R.
Abstract: This article introduces a simplified model for assessing and designing the governance of global health public–private partnerships (PPPs) based on the two concepts of transparency and accountability. The article reviews the literature on partnership governance, which shows many frameworks and recommendations but limited implementation of the proposals. The article proposes a matrix to provide a high-level analytical and planning tool applicable to different types of PPPs in global health. The matrix arranges transparency and accountability as two orthogonal and separate governance dimensions. In the literature, transparency and accountability are two of the most commonly discussed dimensions of governance but they have not been used in this manner to create a model of governance. Transparency is important on its own because it allows learning, contributes to accountability, and shapes organizational performance. Accountability provides a tool to assure that a PPP is achieving its public interest goals and also contributes to improved organizational performance. Both contribute to democracy and public perception. The matrix analyzes transparency and accountability according to three dimensions (relationships, contents, and mechanisms) and assesses the level of each dimension. Using a hypothetical PPP example, the article illustrates how the matrix could be used in practice. The matrix provides a method to assess the levels of transparency and accountability but does not indicate how much of either is good or desirable. The matrix is proposed to improve conceptual clarity and help identify concrete options for action in planning, assessing, and adjusting PPP governance.